Penaklukan Negara atas Agama Lokal Kasus Towani Tolotang di Sulawesi Selatan - Hasse J Hasse J (Al-Ulum, 2012)
This paper is a reflection of the local defense of the religion that had been marginalized by looking further into the state of the local religious marginalization. In its development, the country never abandoned the religion of his intervention. In fact, very close to the state religion. How and through what medium the conquest of the local religion? This question is the focus of this paper by outlining the three sub-themes. First, it is form or variety of ideas in local religious position. Second, the actors involved in local religious positioning. Third, local response, including the existence of local religious elite, associated with differences in religion and culture of the surrounding community. This paper shows that the state has put religion at the ‘manageble’ position. In fact, the position of religion as an important entity is frequently controlled. Similarly, in this paper, it can be found how local communities respond to the presence of local religious so local religion not only placed in the controlled set, but also constantly challenged by the surrounding environment.